2020
DOI: 10.21203/rs.3.rs-124889/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C-Myc Overexpression Increases Ribosome Biogenesis and Protein Synthesis Independent of mTORC1 Activation in Mouse Skeletal Muscle

Abstract: Background: High-intensity muscle contractions (HiMC) are known to increase c-Myc expression which is known to stimulate ribosome biogenesis and protein synthesis in tumor cells. However, whether the increase in c-Myc stimulates ribosome biogenesis and protein synthesis in skeletal muscles remains unknown. Methods: We investigated the effect of adeno-associated virus (AAV)-mediated c-Myc overexpression, with or without fasting or percutaneous electrical stimulation-induced HiMC, on ribosome biogenesis and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Consequently, we reasoned that upregulation of ribosomal activity might ameliorate the cognitive defect caused by CpOGA WT -induced hypo-O-GlcNAcylation. To test this, we increased ribosome biogenesis by overexpression of dMyc [56][57][58] , and observed that dMyc expression in mushroom body could restore local protein synthesis and rescue the hypo-O-GlcNAcylation induced olfactory learning deficit (Figure 4C-4E).…”
Section: O-glcnacylation Affects Cognitive Function Of Drosophila By ...mentioning
confidence: 99%
“…Consequently, we reasoned that upregulation of ribosomal activity might ameliorate the cognitive defect caused by CpOGA WT -induced hypo-O-GlcNAcylation. To test this, we increased ribosome biogenesis by overexpression of dMyc [56][57][58] , and observed that dMyc expression in mushroom body could restore local protein synthesis and rescue the hypo-O-GlcNAcylation induced olfactory learning deficit (Figure 4C-4E).…”
Section: O-glcnacylation Affects Cognitive Function Of Drosophila By ...mentioning
confidence: 99%